(untitled) (Global Journal of Science Frontier Research, 2016)
The study was conducted on The status of an Ethiopian endemic plant Vepris dainellii, in Arba Minch Natural forest, Southern Ethiopia, to determine the population status, population structure and regeneration status of the species. Systematic sampling method was used to collect data from 80 quadrats (20m x 20m) established along transects. Analysis on the structure of the species indicated that the species was under good regeneration status. Anthropogenic activities carried out in the area such as cattle overgrazing, cutting of species for fire wood, charcoal and house construction were the major threats to the species. Therefore, it is recommended that timely measures should be taken by all stakeholders to sustain utilization of the species of the study area.